The association between failure to thrive or anemia and febrile seizures in children between 6 months to 6 years old age - Tavasoli, Azita; soheilipour, fahimeh (Iranian Journal of Child Neurology, 2018)
Objectives: Febrile seizure is the most common seizure disorder in childhood. Anemia or failure to thrive can predispose children to Febrile seizure by affecting the nervous system function. The current study investigates the association between febrile seizures and Anemia or failure to thrive. Materials and Methods: This case-control study was performed on 307children 6 months to 6 years old age hospitalized at the Ali Asghar children`s Hospital from 2011 to 2014 divided into two groups: a case group including 158 children with febrile seizures and a control group including 149 febrile children without seizure. The amount of Hgb, Hct, RBC count, MCV, MCH, and MCHC was recorded and weight-for-age and weight-for-height was calculated based on the WHO Z-Score charts.The date were compared between two groups. Results: There were no differences regarding age and sex between the groups. Statistically significant differences were found regarding the mean RBC count between the case group (4.38×106 ± 0.72×106) and the control group (4.24×106 ± 0.84×106) (p=0.013), as well as about the mean MCV that was 78.73 ± 0.97 and 76.78 ± 1.00 in the case and control groups respectively(p=0.005). Anemia was seen in 28.5% of the case and 42.3% of control group which was statistically significant (p=0.012). There was not statistically significant difference regarding failure to thrive between two groups. Conclusion: in children with febrile seizures anemia was lower comparing with febrile children without seizure. Moreover, there was not any association between failure to thrive and febrile seizures.